Cardiovascular disease risk factors assessment and glycemic control among type-2 diabetes mellitus patients : a comparative study between primary care and diabetic specialist clinic in Kuantan, Pahang - Abdullah, Fa’iza; Tin , Myo Han; Md Aris, Mohd Aznan; Osman, Iskandar Firzada (Academy of Family Physicians of Malaysia and Family Medicine Specialist Association, 2015)

(untitled)
Type-II Diabetes Mellitus (T2DM) patients have high prevalence of cardiovascular disease (CVD) and high morbidity and mortality. They present with other co-morbidity and suffer from its complications. Thus, modifiable cardiovascular risks assessment and glycaemic control should be analyzed for prevention and early intervention.